Paramylon from Euglena gracilis Prevents Lipopolysaccharide-Induced Acute Liver Injury - Xie, Yunhao; Li, Jin; Qin, Huan; Wang, Qing; Chen, Zixi; Liu, Chengyu; Zheng, Ling; Wang, Jiangxin (Frontiers in Immunology, 2022)
Acute liver injury (ALI) is a life-threatening syndrome with high mortality and lacks effective therapies. Rodents under LPS (lipopolysaccharide)/D-Gal (D-galactosamine) stress mimic ALI by presenting dramatically increased inflammation and cell death in the liver. Euglena gracilis, functioning like dietary fiber, is commonly used as a paramylon (Pa)-rich nutritional supplement that has various biological effects such as regulating immune system, anti-obesity, and anti-tumor. Here, we found that Pa or sonicated and alkalized paramylon (SA-Pa) alleviated the LPS/D-Gal-induced hepatic histopathological abnormalities in mice. Compared with Pa, SA-Pa had lower molecular weights/sizes and showed better efficacy in alleviating injury-induced hepatic functions, as well as the transcriptional levels of inflammatory cytokines. Moreover, SA-Pa treatment promoted M2 macrophage activation that enhanced the anti-inflammatory function in the liver, and downregulated STAT3 target genes, such as Fos, Jun, and Socs3 upon the injury. Meanwhile, SA-Pa treatment also alleviated apoptosis and necroptosis caused by the injury. Our results demonstrated that SA-Pa efficiently protected the liver from LPS/D-Gal-induced ALI by alleviating inflammation and cell death.